Differentiated Instruction in English Lessons: Teacher Challenges - Azzahra, Kholifatur Riza (Universitas Pahlawan Tuanku Tambusai, 2024)
The 2013 curriculum has been replaced by the Merdeka Curriculum, which is now implemented at all levels of education in Indonesia. The change has made implementing curriculum changes in the Indonesian education system difficult. This study aims to determine the challenges teachers face when implementing differentiated learning in the Merdeka Curriculum and determine how teachers overcome these challenges. This research was used qualitative method, and the data collected by the researcher is carried out through observation activities and interviews with English teachers in grade 8 MTs Negeri 8 Banyuwangi. This research activity shows the results of the study that teachers faced several challenges when implementing differentiated learning in the Merdeka Curriculum. These challenges include limited facilities for learning activities, students’ lack of desire to learn, and the need for stability in implementing differentiated learning. Teachers faced these challenges by providing technology-based learning and adapted the learning materials which related to students’ daily lives. In implementing differentiated learning, teachers face some obstacles or challenges, so the right strategy is needed to overcome these problems